2022
DOI: 10.3389/fpsyg.2022.920395
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Academic Engagement in Post-graduate Students: Assessing the Role of Positive Emotions, Positive Psychology, and Stress

Abstract: AimThe current study attempted to assess the effect of positive emotion on post-graduate students’ psychological capital (PsyCap) as well as on their academic engagement behavior. Also, the direct relationship between PsyCap and academic engagement behavior was assessed alongside the presence of Stress as a moderating variable between PsyCap and academic engagement behavior amongst post-graduate students in Malaysia.Materials and MethodsA self-administered questionnaire was used for data collection from 373 po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 70 publications
1
15
0
Order By: Relevance
“…Then, the SPSS Amos program (version 21.0) was used to evaluate the mediating effect of EI on BPNS and academic engagement. The present study is based on the structural equation modeling (SEM) technique, which is a nominal research analysis approach ( Saleem et al, 2022 ). For the mediation analyses, a bootstrapping method was further used to obtain bias-corrected 95% confidence intervals (95% CI) with 5,000 re-samples.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, the SPSS Amos program (version 21.0) was used to evaluate the mediating effect of EI on BPNS and academic engagement. The present study is based on the structural equation modeling (SEM) technique, which is a nominal research analysis approach ( Saleem et al, 2022 ). For the mediation analyses, a bootstrapping method was further used to obtain bias-corrected 95% confidence intervals (95% CI) with 5,000 re-samples.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, facilitating engagement has also been revealed to reduce the adversarial impact of sociodemographic predictors on student performance ( Lei et al, 2018 ). So far, research have showed that both personal variables and social-contextual variables could influence the student’ academic engagement ( Patrick et al, 2007 ; Wu et al, 2010 ; Stoeber et al, 2011 ; King and Ganotice, 2014 ; Kilday and Ryan, 2019 ; MacCann et al, 2020 ; Virtanen et al, 2020 ; García-Martínez et al, 2022 ; Luo and Luo, 2022 ; Saleem et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…POA “positive affect” was positively correlated with SEL “self-efficacy,” RES “resilience,” and OPT “optimism,” while NEA “negative affect” was negatively correlated with RES “resilience.” These results are consistent with a published study reporting that positive affect and PsyCap are positively associated, and that the opposite is true for the relation between negative affect and PsyCap ( 32 ). Other previous studies have also found that positive affect exerts a positive effect on PsyCap ( 77 , 78 ). In the fine-grained exploration of the pathways between affect and PsyCap carried out in the present study, positive affect was associated with self-efficacy.…”
Section: Discussionmentioning
confidence: 51%
“…Thus, programs offered at colleges and universities should aim to enhance these aspects of psychological health on the assumption that they are tightly interwoven and could facilitate students’ academic outcomes and overall well-being. The accumulation of positive psychological resources may not only help individuals to enhance their performance in academic setting [ 74 ] but also protect them against pathology [ 75 ]. By exploring individual inner qualities and strengths, the risk of students developing disorders that impact their academic career (such as depression, anxiety, and eating disorders) could be minimized.…”
Section: Discussionmentioning
confidence: 99%